2008
DOI: 10.1111/j.1526-4610.2007.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

A Migraine Prophylaxis Educational Intervention in a Medicaid Population

Abstract: Following an educational intervention for Idaho Medicaid patients identified through retrospective DUR, a trial of a migraine prophylactic drug was initiated for approximately one-third of potential candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…5,28,29,32 Additionally, each of the 4 programs that provided educational materials alone were found to have little to no impact on measured outcomes. 24,44,50,51 It should be noted that one program that reported positive outcomes used prescriber feedback in combination with patientidentifying data and educational material. 23 Along with providing educational material for prescribers, several programs also included supplemental educational material for patients.…”
Section: Zuckerman Et Al (2004)mentioning
confidence: 99%
See 4 more Smart Citations
“…5,28,29,32 Additionally, each of the 4 programs that provided educational materials alone were found to have little to no impact on measured outcomes. 24,44,50,51 It should be noted that one program that reported positive outcomes used prescriber feedback in combination with patientidentifying data and educational material. 23 Along with providing educational material for prescribers, several programs also included supplemental educational material for patients.…”
Section: Zuckerman Et Al (2004)mentioning
confidence: 99%
“…Response rate among reporting programs ranged from 25% to nearly 90%. 2,9,10,12,14,18,20,21,27,29,32,46,[48][49][50] Generally, recipients viewed the intervention positively and often indicated intent to alter therapy based on the materials received. The majority of programs that reassessed patient profiles following response from mailings reported that an actual change in therapy occurred in approximately 50% of patients whose prescriber indicated intent to modify treatment.…”
Section: Zuckerman Et Al (2004)mentioning
confidence: 99%
See 3 more Smart Citations